36. TWO HEALTHY BABIES BORN AFTER IMPLANTATION OF MULTIPLE CHROMOSOMALLY-RESCUED OOCYTES. (August 2019) - Filippini, G.; Fiandanese, N.; Risch, L.; Jemec, M.; Bellavia, M.
Abstract : Introduction: Meiotic rescue is a well-known phenomenon but little is known about live births after oocyte rescue, because of the shortage of data on PB biopsy. PGT-A has been performed for many years to increase the chance of pregnancy, especially in older women. Embryo aneuploidy is a major cause of pregnancy failure and is largely of maternal meiotic origin (>95%), with the risk increasing exponentially from approximately 35 years of age. Molecular analysis of polar bodies provides indirect assessment of an oocyte's chromosomal status by determining whether the chromosomes correctly segregated during meiosis I and II. In about one third of cases, missegregation of one or two chromosomes in meiosis I can be rescued in meiosis II, leading to a euploid oocyte. We present two cases of healthy babies born after single and double chromosome-rescued oocytes Material and methods: A 42- (case 1) and a 44-year old woman (case 2) underwent ART treatment with PGT-A PB, after histories of 3 and 2 prior ART failures respectively. Both couples underwent ICSI with first and second PB biopsy and comprehensive chromosome analysis by Array-CGH. The mechanisms leading to missegregation in PB1 and PB2 (nondisjunction or premature separation of sister chromatids (PSSC)) were analysed using chromosome-specific STRs. Results and conclusions: Case 1: a single euploid fertilized oocyte was transferred, after double rescue of chromosomes 3 and 18 (PB1 -3, -18; PB2: +3, +18) at day 2, resulting in a singleton pregnancy. Case 2: a single euploid fertilized oocyte was transferred after rescue of chromosome 16 (PB1: -16; PB2:+16) at day 3. In case 1, the aneuploidy of chromosomes 3 and 18 in the first PB was caused by PSSC followed by the extrusion of 2 homologous chromosomes in the second PB. In case 2, chromosome 16 underwent PSSC and extrusion of a single chromatid in PB1, followed by nondisjunction in meiosis II and extrusion of two sister chromatids in PB2. In both cases, the rescued oocyte was the only euploid oocyte out of 12 retrieved and they were competent for generating a pregnancy. The two women gave birth at term to healthy babies (a girl of 3280 g and a boy of 3500 g). To our knowledge, this is the first report of healthy births after a multiple chromosomally-rescued oocyte. PGT-A of PBs is a valid method with the limitation of detecting only maternal aneuploidies and so is appropriate for screening of older women. Analysis of the 2 polar bodies by aCGH is valuable not only for aneuploidy screening in ART for older women, but also to understand the mechanisms leading to missegregation and rescue in oocytes.